Individual service excellence for better performance: evidences from MUET students / Boo Ho Voon, Joyce E. C. Voon and Ai Kiat Teo - Boo, Ho Voon; Joyce E., C. Voon; Ai, Kiat Teo (UiTM Cawangan Kedah, 2021)
An individual's attitude is imperative in sustaining his/her performance. One has to believe and do the right things all the times for excellence. However, there are many aspects that the individual needs to recognize and do excellently well. This paper presents an attitudinal measurement on service excellence attitudes and links it to the students’ MUET performance. The multi-item measurement scale was systematically developed and empirically tested for reliability and validity. The individual’s service excellence scale was called MyServEx (My Service Excellence) which consisted of 6 dimensions and 32 items. The MyServEx (Self) was empirically tested and the survey data were obtained from the MUET students to investigate the role of attitudes in leveraging the English language performance. The teachers can understand the students better and creatively help them. The limitations and future direction for research were also discussed.